Graphene Oxide Applications and Opportunities - Kamble, Ganesh (IntechOpen, 2018)
This book aims to introduce the emerging technologies of graphene oxide (GO) in various fields such as industrial, medical, electronics, artificial intelligence, materials-alloys, energy storage devices, optical, physics, mechanical, nanomaterials, and sustainable chemistry. At the current level of development, the properties and binding structure of graphene are important toward the recent applications. The knowledge produced by the graphene oxide could be a much haunting basis for discovering innovative opportunities in the field of emerging trends of research. Future technology expected that the full development will depend only on graphene and its functionalized composite materials. This book highlights the challenges and opportunities associated with GOs. Subject of interest in this book is exploring the opportunities and technologies related to abundant clean energy, pure water, and noble long healthy life.